Rancang Bangun IoT Based Monitoring System pada Multi Conveyor Untuk Perpindahan Benda - Erdani, Yuliadi; Maulana , Gun Gun; Farhan, Abiyyu (The Indonesian Journal of Computer Science, 2024)
Multi-conveyor systems are prone to transfer point failures that disrupt transportation routes and create production bottlenecks. Continuous monitoring and supervision are required, but manual methods are time-consuming, costly, and cause delays. Integrating IoT with belt conveyors enables mobile app-based monitoring, allowing real-time access to sensor information, continuous monitoring, and immediate error correction. This study aims to design and implement an IoT-based monitoring system to detect jams and overturned objects on multi-conveyors transferring objects at 90-degree angles. Using the VDI2206 methodology, the study ensures precise product definition and accurate estimates in all design phases. The system minimizes transfer distances between conveyors, employs precise sensors, and uses control algorithms for ongoing transfer process monitoring. An intuitive user interface allows real-time sensor data and animation monitoring. Two ESP32 microcontrollers coordinate sensor functions and data communication, achieving an average response time of 449.508 ms. This efficient system improves industrial conveyor monitoring, reducing manual monitoring time and costs.